Inoculation frequency and maize genotype influence plant growth-promoting effects of soil bacteria under low nitrogen conditions - Foster, Lexie R.; Yang, Jinliang; Riethoven, Jean-Jack M.; Mukhtar, Hussnain; Schachtman, Daniel P. (Frontiers in Plant Science, 2025)
Global agriculture relies heavily on the use of synthetic nitrogen fertilizer to meet the current global food demand. Unfortunately, the average nitrogen-use efficiency (NUE) of maize (Zea mays ssp. mays) is as low as 50%. Improving the NUE of maize is essential for feeding the ever-increasing world population while also decreasing the negative environmental impacts of nitrogen fertilizer due to runoff and volatilization. Harnessing the symbiotic relationship between plants and soil microorganisms may be one method for increasing the NUE in crops such as maize. In the present study, a set of potentially beneficial bacterial species chosen based on genetic information from the host was investigated for their ability to improve NUE-related traits in maize grown under nitrogen-deficient conditions. This was carried out through non-repeated and repeated bacterial inoculations using different maize genotypes. We identified several growth-promoting bacterial isolates and observed a significant interaction between the bacterial isolates and the maize genotype, suggesting a strong interaction between the host genetics and the effects of bacterial isolates. In addition, our results showed a significant growth response to repeated inoculations with a beneficial bacterial isolate. In summary, when evaluating the plant-growth-promoting effects of a bacterial species, it is essential to consider the interaction between host plant genotype and bacterial isolate. In addition, when inoculating with bacterial isolates, multiple inoculations appear to be more effective than a single inoculation after bacterial seed priming.